Construction Criminal Sanctions On Violators of The Moratorium Palm Oil Company License With Plea Bargaining - Safitri Wikan Nawang Sari; Masrudi Muchtar; Andien Sofyanoor (Faculty of Law, Universitas Pekalongan, 2022)
Phenomena related to the clearing of oil palm plantations by companies as corporations or legal entities for the South Kalimantan Regional Government as a form of regional development to be more advanced but Corporate Social Responsibility (CSR - Corporate Social Responsibility) to the environment and surrounding communities is sometimes ignored or not implemented because the use of Natural Resources in the region is exploited. Reflecting on the events of environmental degradation in South Kalimantan which led to events floods as well as forest and land fires (Karhutla), then to restore health and environmental sustainability in the province of South Kalimantan is fitting Presidential Instruction No. 5 year 2019 on the termination of the granting of new permits and improving the governance of primary natural forests and peatlands should be extended again. So to overcome this, the government must play an active role either through criminal law policies as outlined in the legislation or with the application of criminal law legislation in law No. 39 year 2014 on plantations more oriented to sustainable ecological development.This study was a normative legal research and formed descriptive qualitative, conducted in the region of South Kalimantan province. This study used statute approach and a concept approach. Data collection from materials primary, secondary and tertiary law were obtained through library studies and documentation studies and then analyzed using grammatical interpretation as well as qualitative empirical juridical analysis techniques. In order for the implementation of plea Bargaining in construction criminal sanctions on violators of the moratorium on permits for oil palm plantation companies as an alternative to solving criminal cases in the field of environment can be included as a draft law to be passed as a separate law, given in law No. 39 year 2014 on the plantation has no arrangement.Keywords: construction, sanction, criminal, violation, permit, moratorium, company, oil palm plantation, plea bargaining.